Awestruck: Natural Interaction with Virtual Reality on Eliciting Awe - Quesnel, Denise; Riecke, Bernhard E. (Poster presented at IEEE Symposium on 3D User Interfaces 3DUI, 2017)
In the study of transformative experiences, the feeling of awe is found to alter an individual's perception in positive, lasting manners. Our research aims to understand the potential for interactive virtual reality (VR) in eliciting awe, through a framework based on collection of physiological data alongside self-report and phenomenological observations that demonstrate awe. We conducted a mixed-methods experiment to test whether VR is effective in eliciting awe, and if this effect might be modulated by the type of natural interaction in the form of a 'flight' lounger vs. 'standing'. Results demonstrate both interaction paradigms were equally awe-inspiring, with overall physiological (in the form of goose bumps with a 43.8% incidence rate) and self-report data (overall awe rating of 79.7%), and females showing more physiological signs of awe than males. Observations revealed 360-degree interaction and operability of hand-held controllers could be improved, with the consequence of designing even more effective transformative experiences.
Keywords: 2-page conference paper; EarthGazement; Riecke; Riecke_2017; TEDx; bernhard-riecke; conferencePapers; denise-quesnel; earthgazing; iat802; iat802_fall2016; overview-effect; short conference paper